Exploring the Complexity of Pan-Cancer: Gene Convergences and in silico Analyses - Teodoro L; Carreira ACO; Sogayar MC (Breast Cancer: Targets and Therapy)
Leandro Teodoro,1,2 Ana Claudia O Carreira,1,3 Mari C Sogayar1,2 1Cell and Molecular Therapy NUCEL Group, School of Medicine, University of São Paulo, São Paulo, São Paulo, 01246-903, Brazil; 2Biochemistry Department, Chemistry Institute, University of São Paulo, São Paulo, São Paulo, 05508-900, Brazil; 3Center of Human and Natural Sciences, Federal University of ABC, Santo André, São Paulo, 09280-560, BrazilCorrespondence: Mari C Sogayar, Institute of Chemistry – University of São Paulo, Prof. Lineu Prestes Avenue, 748 - Cidade Universitária, São Paulo, São Paulo, 05508-000, Brazil, Tel +5511992042844, Email mcsoga@iq.usp.brAbstract: Cancer is a complex and multifaceted group of diseases characterized by highly intricate mechanisms of tumorigenesis and tumor progression, which complicates diagnosis, prognosis, and treatment. In recent years, targeted therapies have gained prominence by focusing on specific mutations and molecular features unique to each tumor type, offering more effective and personalized treatment options. However, it is equally critical to explore the genetic commonalities across different types of cancer, which has led to the rise of pan-cancer studies. These approaches help identify shared therapeutic targets across various tumor types, enabling the development of broader and potentially more widely applicable treatment strategies. This review aims to provide a comprehensive overview of key concepts related to tumors, including tumorigenesis processes, the tumor microenvironment, and the role of extracellular vesicles in tumor biology. Additionally, we explore the molecular interactions and mechanisms driving tumor progression, with a particular focus on the pan-cancer perspective. To achieve this, we conducted an in silico analysis using publicly available datasets, which facilitated the identification of both common and divergent genetic and molecular patterns across different tumor types. By integrating these diverse areas, this review offers a clearer and deeper understanding of the factors influencing tumorigenesis and highlights potential therapeutic targets.Keywords: pan-cancer, tumor therapy, tumor biomarkers